Analisis Kasus Pencemaran Nama Baik (Pelanggaran UU ITE Dan KUHP) Oleh Artis Medina Zein Terhadap Selebgram Marissya Icha - Frinawaty Lestarina Barus; Kristina Damai Yanti Simorangkir; Rysta Vara Nurlette; Rahel Yena Br.Kaban (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research analyzes one case of defamation committed by a Media Zein celebrity on social media. Medina Zein was charged with article 27 paragraph (3) of Republic of Indonesia Law number 19 of 2016 concerning ITE. Defamation is one of the problems in forensic linguistics that often occurs in the real world and cyberspace. Defamation or defamation can be done verbally and in writing. The aim is to bring down someone’s good name and/or embarrass others. This research uses a qualitative descriptive research method. This research contains a general, clear picture and is based on facts that occur in the field regarding what is being researched. This research uses data analysis in which there is an explanation of the perpetrator and the crime he committed. The results of this research stated that sister Medina Zein was found guilty and sentenced on charges of defamation with a sentence of 6 months in prison.